Task Force on Telecommunications Infrastructure in the Arctic (TFTIA), meeting 03, final participants list - Arctic Council Secretariat (Arctic Council Secretariat, 2016)
The Arctic Council's Task Force on Telecommunications Infrastructure in the Arctic (TFTIA) was established by the second Iqaluit Declaration (2015). It held its third meeting in Copenhagen, Denmark in September of 2016.